2015
DOI: 10.1111/imig.12201
|View full text |Cite
|
Sign up to set email alerts
|

Migrant Domestic Workers in Asia: Transnational Variations and Policy Concerns

Abstract: The labour force of the migrant domestic workers (MDWs) has become one of the significant policy concerns in Asia. Most of the Asian countries are not following (or not to an equal extent) the Domestic Workers Convention 2011 (No. 189) which has been adopted by the International Labour Organization (ILO). The objective of this article is to show the transnational variations and policy concerns of the MDWs in Asia. Based on content analysis, the authors found that there are considerable transnational variations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…The point is, a person who migrates from one state to another, with the intention to work for the fulfillment of its right to be called by migrant workers. Meanwhile, according to the International Labor Organization (ILO, 2013) and the International Organization for Migration (IOM, 1009, 12), a migrant domestic worker is someone who is moving to another state or region to life and social conditions are more viable and improve prospects for themselves or family, work in providing services for the workers or for the household (Islam & Cojocaru, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The point is, a person who migrates from one state to another, with the intention to work for the fulfillment of its right to be called by migrant workers. Meanwhile, according to the International Labor Organization (ILO, 2013) and the International Organization for Migration (IOM, 1009, 12), a migrant domestic worker is someone who is moving to another state or region to life and social conditions are more viable and improve prospects for themselves or family, work in providing services for the workers or for the household (Islam & Cojocaru, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Despite the relevance of domestic work, and the importance of home-based care-giving, both nationally and internationally, there is almost no research literature on the experiences and education of women who migrate for domestic work. Most of the literature related to domestic workers focuses on the work conditions, human rights, and legal issues (Blackett, 2012;Choudry & Smith, 2016;Devasahayam & Yeoh, 2007;Elias, 2010;Huang, Yeoh, & Toyota, 2012;Islam & Cojocaru, 2016;Sollund & Leonard, 2012;Suleman, 2015). The social relations of care-work, associated with the household to the function of the labor market in Southeast Asia, provide insights about the development of significant networks of activists, advocacy groups, and NGOs in the region (Carney, 2010;Elias, 2010;Huang, Yeoh, & Toyota, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Outsourcing and subcontracting of domestic care and familial care to caregivers has also increased in several developed Asian countries, in addition to the expansion of the role of the market and voluntary sectors in care provision (Michel & Peng, 2017). Outsourcing domestic work or childcare has become common in Korea, particularly by hiring migrant domestic workers in Hong Kong, Singapore, and Taiwan (Chan, 2005;Choi, 2016;Constable, 2007;Cortés & Pan, 2013;Islam & Cojocaru, 2015;Lan, 2003;Estévez-Abe & Kim, 2013). Recent studies have shown that the frequency, specificity, and uncertainty level of the transaction, as well as social beliefs and preferences can facilitate or hinder outsourcing (Raz-Yurovich, 2014;Kornrich, 2012;Van der Lippe et al, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%